The mediating role of locus of control in the effect of organizational justice on organizational cynicism in school organizations - LEVENT, AHMET FARUK (My University, 2022)
This study aims to examine the mediating role of locus of control in the relationship between organizational justice and organizational cynicism. This study examined the mediating role of the locus of control in the effect of organizational justice on organizational cynicism in school organizations, in a way that includes all personnel who have a direct effect on education and training in schools. This study used the relational survey model, which is one of the quantitative research methods. This study was conducted with 385 participants identified through simple random sampling among teachers working in public schools. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) analyzes of the obtained data were performed using SPSS and AMOS statistical package programs. As a result of the analysis, it was determined that there is a negative relationship between organizational justice and organizational cynicism and that locus of control plays a mediating variable in the relationship between organizational justice and organizational cynicism
Keywords: School Administration; Organizational Justice; Organizational Cynicism; Locus of Control; Mediation Analysis